Short communication. Effect of bemisia tabaci biotype in the transmiáion of Tomato Yellow Leaf Curl Sardinia Virus (TYLCSV-ES) between tomato common weeds - Jiang, Y.X.=700 1 De Blas, C.; Bedford, I.D.; Nombela, G.; Muñiz, M.
(Es, En)
ilus.,22 ref.
Keywords: BEMISIA TABACI; BIOTIPOS; GEMINIVIRUS; ESPAÑA; MOSCA BLANCA